-2-5b=-3b

Simple and best practice solution for -2-5b=-3b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2-5b=-3b equation:



-2-5b=-3b
We move all terms to the left:
-2-5b-(-3b)=0
We get rid of parentheses
-5b+3b-2=0
We add all the numbers together, and all the variables
-2b-2=0
We move all terms containing b to the left, all other terms to the right
-2b=2
b=2/-2
b=-1

You can always share this solution

See similar equations:

| | | Y=3x-9x-27x | | 4x+34=1-6 | | Y=x2-225 | | 12x+3+7x-2=90 | | 7p/10+9=15 | | 2.5x=5x+3 | | 7r-15=2r+10 | | 11=7t/4 | | (2x-10)=-3 | | 50.50+4x=56.10 | | 3x-6=1x-18 | | 12-222x+34=180 | | 3+-1x=-4 | | (5-3n)=4 | | (2x)+58=180 | | (?11/6)+m=-2/9? | | 3.5g+7=1.5g+15= | | -13=20m+5-2m | | 5x-1+15x+1=25x-25 | | 6.68=??2.3c+0.72.3c+0.7 | | -13=22m | | 3y+4=6y-+19 | | -3(b-15)=12b+30 | | 15y-23=6y+3 | | 225=a2 | | {2x-1}{3}=-5=-5 | | d=65+10 | | 2x-6+5x+3=13x-21 | | 10x+9+8x-9=180 | | (3x+96)°=180 | | 4x+11=77 |

Equations solver categories